Research on Intellectual Capital Business Model in China: A Case Study in K Group - ZHU, Nai-xiao; DING, Zhuo-qi (Journal of Comparative International Management)

(untitled) (Management Futures, 2014)
Focus on the practice of intellectual capital business model (ICBM) in high technology enterprises in China would be very important to the development of Chinese economic reform. The case study of K Group shows that we should examine the intellectual property right (IPR) protection system from three-dimensional perspective constituting law, economics and management to fully understand the ICBM. Policy recommendations following for the analysis can then help Chinese high technology enterprises strengthen their international competitiveness and raise their IPR protection level higher in the future.